Brazilian diplomacy and the legitimization of the Brazilian military dictatorship in the international arena (1964-1974) - Castilho, Alessandra Beber (2022)
This dissertation aims to analyze the role of Brazilian diplomacy in legitimizing the Brazilian Military Dictatorship (1964 1985) abroad. We hypothesise that the autonomy of the Ministry of Foreign Affairs (MRE), also known as Itamaraty, during the dictatorship period was due to the inherent conservatism of its structures and that there was a collaboration between sectors of the diplomatic corps with the authoritarian project of the military dictatorship. In this way, we seek to show not only how the diplomatic apparatus was used for purposes of public relations and propaganda abroad, but also the extent of the collaboration of sectors of the diplomatic corps in the elaboration of the dictatorship\'s external communication strategy. Through extensive documentary research, this work will focus on the strategies used to circumvent the image of Brazil after the promulgation of Institutional Act no. 2, in 1965, and Institutional Act no. 5, in 1968. We believe that this thesis, by analyzing the role of the diplomatic corps in defending the image of the military dictatorship during its most authoritarian period, governed by the so-called hard-line, will contribute to understanding the depth of the relationship between Itamaraty and the Armed Forces and the influence of certain ideologies in the formulation of foreign policy, especially during the Cold War period.